PRODUCTION OF IMMUNORADIOMETRICASSA Y (IRMA) CA 15.3 KIT COMPONENT FOR DETECTION OF BREAST CANCER - Widayati, Puji; Ariyanto, Agus; Sutari, Sutari; Mondrida, Gina; Darwati, Siti (Jurnal Radioisotop dan Radiofarmaka, 2008)
PRODUCTION OF IMMUNORADIOMETRICASSA Y (IRMA) CA 15.3 KITCOMPONENT FOR DETECTION OF BREAST CANCER. YKI has ranked that breast cancer as a second deseas in causing death of Indonesian women (, 2007). This phenomenon has been caused by the low level of public awareness in early detection of cancers. As a consequences this kind of cancer has generally been diagnosed in advanced stadium which is difficult to be treatedÂ In spite of this, the disease actually can be detected early by measuring level of CA 15.3, a tumor marker for breast cancer. One of such in vitro method is immunoradiometricassay (IRMA) for CA 15.3. The CA 15.3 itself is a glycoprotein of heterogen compound capable of reacting with monoclonal antibody CA 15.3. Production of the IRMA CA 15.3 kit has been performed in the Center for Radioisotope and Radiopharmac.eutical, National Nuclear Energy Agency of Indonesia. Optimization of the kit component has been carried out using several parameter including type ofmonoclonal antibody for tracer and buffer coating type. The results showed that monoclonal anti CA M37901M type is better than M37552M type for tracer production. The M3790lM gave yield about 79.51%, with specific activity 29.12 Ci/ g, radiochemical purity 94.21% and %B/T about11.94%. Several buffers have been evaluated and 0.05 M pH 9.6 carbonate bicarbonate buffer showed the highest specific binding when it was used as coating buffer. Preparation of IRMA CA 15.3 standard solution gave a linier relation between CA 15.3 concentration and the maximumbinding (%B/T) Y=0.227X+0.5177 and correlation coefficient R 0.9840Keywords: Radioimmunoassay, Immunoradiometricassay, tumor marker, CA-15.3